Integrated approaches for plastic waste management - Kherdekar, Rajkumar D.; Ade, Avinash B. (Frontiers in Microbiology, 2024)
Plastic pollution is the challenging problem of the world due to usage of plastic in daily life.Plastic is essential for packaging food and other goods and utensils to avoid the risk of microbial attack. Due to its hydrophobic nature it is used for wrapping as laminates or packaging liquid substances in pouches and sachets. The tensile strength of the plastic is more therefore it is used for manufacturing carrying bags which can bear heavy load. Plastic is available in various forms as per the requirements in our daily life. Annually millions to trillions of polyethene carry bags are being manufactured and utilized throughout the world. The plastic requires millions of years for natural degradation. The physical and chemical processes are able to degrade plastic material at the meager level by 200 to 500 years in natural conditions. Many industries focus on recycling of plastic. Biodegradation is a comparatively slow and cheaper process that involves microbes.To dispose of plastic completely there is a need of an integrated process in which all the possible methods of disposal are involved and used sustainably so that minimum depletion occurs to the livestock and the environment. In the current review, we could try to emphasize the intricate nature of plastic polymers, pollution caused by it and possible mitigation strategies for plastic waste management.